2011
DOI: 10.1007/s00374-011-0645-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of invasion of Mikania micrantha on germination of rice seedlings, plant richness, chemical properties and respiration of soil

Abstract: Mikania micrantha, a creeper and climber, has invaded forests and agricultural areas in the Western Ghats. A quantification of the effect of Mikania on species richness and factors that contribute to its success would help to understand the invasion success of Mikania in the Western Ghats of India. This study investigated its impact on species richness and factors that contribute to its invasion success. Impact of Mikania on species richness was studied in areas invaded by Mikania and not yet invaded by Mikani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…The second study area was very disturbed due to human as well as natural interferences (flooding) and higher disturbance degraded the habitat and made it unsuitable for many species and brought about the variation in species composition even in a small area. In addition the encroachment and increasing Mikania cover is the another reason for lower plant species diversity (Kaur et al 2012). This is also supported by the correlation analysis between invasion and species richness.…”
Section: Vegetation Compositionsupporting
confidence: 59%
See 1 more Smart Citation
“…The second study area was very disturbed due to human as well as natural interferences (flooding) and higher disturbance degraded the habitat and made it unsuitable for many species and brought about the variation in species composition even in a small area. In addition the encroachment and increasing Mikania cover is the another reason for lower plant species diversity (Kaur et al 2012). This is also supported by the correlation analysis between invasion and species richness.…”
Section: Vegetation Compositionsupporting
confidence: 59%
“…Many studies have already recorded that the alien invasion is harmful for the native species diversity (Kaur et al 2012). This study also found similar results for the invasive plant Mikania micrantha H.B.K.…”
Section: Invasion and Species Richnessmentioning
confidence: 99%
“…The pH and electrical conductivity of soil/fly ash were determined in distilled water suspension (1:5 wt/vol), prepared by shaking for 1 h and filtering through Whatman filter paper #1, using digital pH meter (Mettler Toledo, Switzerland) and conductivity meter (Metrex Ltd., India) (Kaur et al, 2012). Contents of PO 4 -P and NO 3 -N were determined by molybdenum-blue method (Allen, 1989) and salicylate blue method (Anderson and Ingram, 1993), respectively.…”
Section: Nutrient and Elemental Analysismentioning
confidence: 99%
“…Unfortunately, applying the same control methods to every occurrence of a broadly adapted weed can be ineffective and costly (Bhagwat et al ., ). Mikania micrantha is an ideal example of the importance of applying diverse management approaches, as it is found in a broad range of habitats across its invaded range (Zhang et al ., ; Kaur et al ., ; Day et al ., ). Mikania micrantha is now found in 20 Pacific islands and territories (PICTs; Day & Winston, ) and most countries in south and south‐east Asia (Day et al ., ).…”
Section: Introductionmentioning
confidence: 99%